Cephalometric Evaluation of The Patients with Osas: Uvulo-Glossophareyngeal And Cervico-Craniofacial Skeletally Morphology - Sıla Mermut Gökçe; Serkan Görgülü; Hasan Suat Gökçe; Ali Osman Bengi; Timur Akçam (Galenos Yayinevi, 2012)
Aim:In the current study, it was aimed to determine the importance of the cephalometrical radiographic evaluation for the localization of posterior airway obstruction in patients with obstuctive sleep apne syndrome (OSAS).Subjects and Methods:Cephalometric radiographs were obtained from 61 patients diagnosed with OSAS (27 females, 34 males) to assess the uvulo-glossofarengeal and cervico-craniofacial skeletal morphology. These measurements were compared with the cranial and pharyngeal values of skeletally Class 180 healthy individuals' (36 females, 44 males) standard lateral cephalographs.Results:The length of the soft palate (P-Pm) in OSAS patients was found significantly greater than the control group. The thickness of the soft palate in midsagittal plane (x-y) in OSAS patients was found significantly greater than the control group. In OSAS patients, hyoid bone localized significantly to inferior than the control group; the tongue height (TH-Z) was significantly greater in patients with OSAS than the control group. At all levels of pharyngeal airway in the anteroposterior direction (af1-pf1, af2-pf2, af3-pf3, af4-pf4), significant narrowing were found in the OSAS subjects. One of the most significant finding was an extension of the head position in accordance with increased cranioservical angle in OSAS patients.Conclusion:OSAS patients' posterior airway distance narrowed at all levels from nasopharynx to hypopharynx. The craniofacial and pharyngeal anatomy of OSAS patients can be examined in detail by lateral cephalometry and cephalometric examination is an important contribution of OSAS diagnosis.